KEDUDUKAN FATWA DSN DALAM TATA HUKUM NASIONAL - Ichwan Ahnaz Alamudi; Ahmadi Hasan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The Sharia economy grows in line with the demands of the Muslim community, which wants an economy that competes with the capitalist economy. Of course this struggle is not as easy as turning your palms. Political, sociological, huokum struggles also colored the emergence of regulations that banks Shariah in Indonesia. With the system of non-Islamic states, it must be difficult for the sharia banking to conduct transactions in accordance with the law of fiction that is written in the Islamic books. The product of the sharial banking that is